1984
DOI: 10.1029/jb089ib07p06111
|View full text |Cite
|
Sign up to set email alerts
|

Structure and variability of oceanic crust on the flanks of the East Pacific Rise between 11° and 13°N

Abstract: We use over 500 seismograms collected by five ocean bottom seismometers to examine the structure and variability of 0.5-m.y.-old crust in the Rivera Ocean Seismic Experiment (ROSE) area of the East Pacific Rise between 11 ø and 13øN. There are no significant differences among the first arrival travel times for 10 independent refraction line segments along the isochron. Amplitude patterns recorded on the individual lines, however, suggest that structural boundaries within the upper crust vary by hundreds of met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
65
0

Year Published

1986
1986
2007
2007

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(71 citation statements)
references
References 31 publications
6
65
0
Order By: Relevance
“…In general, the V p /density gradient of Layer 2 largely reflects lithological variations in the uppermost crust and diminishing alteration and porosity/fracturing of igneous rocks with depth (Bratt and Purdy, 1984;Detrick et al, 1994). The physical properties of Layer 3 and those of the underplated bodies are thus considered to be a good proxy for those of the mostly unaltered, crack-free gabbroic rocks that probably predominate at lower crustal levels (e.g.…”
Section: Structure and Physical Properties Of Igneous Provincesmentioning
confidence: 99%
“…In general, the V p /density gradient of Layer 2 largely reflects lithological variations in the uppermost crust and diminishing alteration and porosity/fracturing of igneous rocks with depth (Bratt and Purdy, 1984;Detrick et al, 1994). The physical properties of Layer 3 and those of the underplated bodies are thus considered to be a good proxy for those of the mostly unaltered, crack-free gabbroic rocks that probably predominate at lower crustal levels (e.g.…”
Section: Structure and Physical Properties Of Igneous Provincesmentioning
confidence: 99%
“…Since Houtz and Ewing [1976] first documented an age-dependent increase in the velocity of the uppermost crust, several studies have confirmed this relationship. In the Pacific alone, these studies include conventional refraction [Spudich and Orcutt, 1980;Purdy, 1982;Bratt and Purdy, 1984;Bratt and Solomon, 1984;McClain and Atallah, 1985;Bee and Bibee, 1989;, borehole [Stephen and Harding, 1983;Little and Stephen, 1985;Duennebier et al, 1987;Whitmarsh et al, 1987;Collins et al, 1989], single-ship Tolstoy et al, 1997] and two-ship multichannel [Harding et ai., 1989;Vera et ai., 1990], and on-bottom seismics [Christeson et ai., 1994a]. Sensitivity to velocities immediately beneath the seafloor varies between methods.…”
Section: Aging Of Extrusive Crustmentioning
confidence: 99%
“…Crustal Age (Myr) [Linear] Extrusive V vs. Age (<l) [Purdy, 1982;Bratt and Purdy, 1984;Bratt and Solomon, 1984], Capricorn (I» [McClain and Atallah, 1985], Hole 504B (0) [ Stephen and Harding, 1983;Little and Stephen, 1985;Collins et al, 1989], ESP studies at the northern EPR (_) [Harding et al, 1989;Vera et al, 1990], multichannel studies at the southern EPR (T) Tolstoy et al, 1997], EXCO (.) , NOBEL (~) [Christeson et al, 1994a], and this study (*).…”
Section: Aging Of Extrusive Crustmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 5 shows the basalt velocity-depth relationship with the measured seismic velocities. For comparison, the P-wave velocities of INL basalts are more consistent with that of ocean floor basalts (e.g., Purdy 1982;Bratt and Purdy 1984;Wilkins et al 1991) Basalt and Rhyolite Density-Depth Relationship -The starting basalt density was anchored to the average density calculated for basalt measurements at the near surface. The density-depth relationship was extended from this value at the surface to a depth of 1100 m using basalt density measurements in drill holes 2-2A, INEL-1, and WO-2 (Figure 6).…”
Section: Velocity and Density Depth Relationshipsmentioning
confidence: 99%